(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background and Objectives: Accurate preoperative staging is paramount in colon cancer management. While abdominal CT is the primary imaging modality for local staging, its diagnostic accuracy for identifying high-risk disease (T3/T4 tumors, nodal involvement) remains variable. The aim of this study is to find out the diagnostic accuracy of abdominal CT in local staging of colon cancer patients, by comparing CT findings with histopathological analysis as the gold standard method at the Dow Institute of Radiology (DIR). Methods: This cross-sectional study included 151 patients aged 18-50 years with newly diagnosed colon cancer scheduled for surgery. All participants underwent contrast-enhanced abdominal CT. CT findings were interpreted independently by two radiologists blinded to histopathological results. A tumor was classified as high-risk on CT and histopathology based on predefined criteria for T-stage, N-stage, and extramural venous invasion. Results: The study demonstrated that CT scan had a sensitivity of 76.7%, a specificity of 84.6%, and an overall diagnostic accuracy of 80.1% for identifying high-risk colon cancer. Stratified analysis revealed higher accuracy in females (86.5%), younger patients (18-34 years, 82.7%), and tumors located in the sigmoid colon (88.4%) and rectosigmoid junction (88.0%). Conclusion: Preoperative abdominal CT shows substantial diagnostic accuracy for local staging of colon cancer, proving to be a reliable tool for identifying high-risk disease. Its high specificity makes it particularly valuable for ruling out advanced stages, thereby playing a critical role in initial therapeutic decision-making.